Cardiac biopsy with intracardiac echocardiographic guidance for successful diagnosis of cardiac lymphoma. Issue 9 (9th July 2018) - Katagiri, Seiichiro; Akahane, Daigo; Suguro, Tamiko; Furuya, Nahoko; Fujimoto, Hiroaki; Saito, Tetsushi; Yamashita, Jun; Nakamura, Naoya; Ohyashiki, Kazuma
Key Clinical Message: The diagnosis and appropriate treatment of cardiac lymphoma are often delayed by the difficulty in obtaining heart tissue biopsies. Intracardiac echocardiography‐guided biopsy can improve the prognosis of cardiac lymphoma by decreasing postbiopsy complications and increasing biopsy quality, allowing collection of sufficient material for multilateral analysis. Abstract : The diagnosis and appropriate treatment of cardiac lymphoma are often delayed by difficulties in obtaining heart tissue biopsies. Intracardiac echocardiography‐guided biopsy can improve the prognosis of cardiac lymphoma by decreasing postbiopsy complications and increasing biopsy quality, allowing collection of sufficient material for multilateral analysis.